Metaphysics and Universality - Šliogeris, Arvydas (Problemos, 2004)
The article addresses a question that has been of major interest during the whole history of the European metaphysics: it is the question about the origin of universality. This article discusses two interpretive options of the traditional metaphysics that author describes as the deductive and inductive approaches to the origin of universality. According to the first approach, universality is derived from human sensual experiences and is equated with generalisation. According to the second approach, universality is an a priori granted to the human intellect. An author focus on the weaknesses of both approaches and emphasizes a radical separation of universality and generality. The author suggests a hypothesis that the only origin and source of universality is a kind of absolute a priori – exceptionally human experience of Nothingness as a metaphysical givenness that the author denominates „extuition of Nothingness“. Universality is considered to be a unique human experience of Nothingness that is concentrated in words which have no sensual reference and therefore are peculiar words – categories, the names of Nothingness.
Keywords: generality; universality; reductionism; inductionism; Nothingness